The effect of pelvic floor muscle training and perineal massage in late pregnancy on postpartum pelvic floor function in nulliparas: A randomised controlled clinical trial - RuiJu He; XiaoXiao Wang; SongWen Nian; XiaoQing Wang; Lei Zhang; Ye Lu (Elsevier, 2023)
Objective: To evaluate the effects of pelvic floor muscle training (PFMT) and perineal massage during late pregnancy on postpartum pelvic floor function in nulliparas. Design: Randomised controlled trial. Setting: The Peking University First Hospital, a teaching hospital in China. Participants: Two-hundred nulliparas were included. Interventions: Nulliparas were randomised into four groups in a 1:1:1:1 ratio. Group A, control; group B, perineal massage; group C, pelvic floor muscle training (PFMT); group D, perineal massage and PFMT. The intervention group received the corresponding intervention from 34 weeks of gestation until delivery. Measurements: Changes in pelvic floor function from 34 weeks of gestation to 6 weeks postpartum were assessed using pelvic floor electromyography (EMG), pelvic organ prolapse quantitation (POP-Q), and pelvic floor distress inventory-20 (PFDI-20). Results: Those with PFMT (groups C and D) had a smaller decline in pelvic floor EMG of fibre II than those without PFMT (groups A and B) [− 0.2 (− 7.1, 11.3) µV vs 6.1 (− 0.2, 15.2) µV, P = 0.040]. The same scenario was observed in the pelvic floor EMG of fibre I. The Aa point measurement differences of those with PFMT (groups C and D) were smaller than those without PFMT (groups A and B) [0.0 (0.0, 2.0) cm vs 1.0 (0.0, 3.0) cm, P = 0.006]. The same result was observed for point Ba. No difference was observed in EMG and POP-Q in nulliparas with (groups B and D) or without perineal massage (groups A and C). No differences were observed in PFDI-20 scores. Key conclusions: PFMT during late pregnancy enhanced pelvic floor EMG, while perineal massage alone or PFMT combined with perineal massage did not. Implications for practice: PFMT in late pregnancy enhances pelvic floor function.